Sândi vocálico externo no Poruguês Arcaico - Cangemi, Ana Carolina Freitas Gentil Almeida [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This thesis aims to study the processes of external phonological vocalic sandhi in 13th century Archaic Portuguese (AP). These processes are diphthongization, V1 elision, crasis and deletion or nonproduction of V2 and will be analyzed in 200 Cantigas de Santa Maria (CSM) from the point of view of the Nonlinear Phonology theories. The CSM are a collection of 420 chants in praise to Virgin Mary compiled in Galician- Portuguese by Alfonso X (1211-1284). We started from the scansion of the CSM verses, verifying the location of stresses and clarifying doubts about the word's delimitation in AP. The methodology aims to abstract the limits between words by from the scansion of the verses in poetic syllables and from the metrification patterns present in the CSM. The rhythmic and phonotactic contexts of application of the processes of external phonological vocalic sandhi constitute the core of our study, which extends itself to the analysis of hiatus occurrences. In the first phase of Portuguese language the results achieved reveal that the phonological processes which undo the hiatus structure nowadays started to act already in AP. Besides, those processes were expressive in AP, for instance: the elision has an application margin close to the vowels maintenance when compared to hiatus (the permanence of two vowels which are involved in word junctioncontext). Both elision and hiatus were more productive at that moment of the language than diphthongization, crasis and deletion or nonproduction of V2, which were marginal phonological processes, with more restricted application contexts. These facts are due to rhythmic, prosodic and phonotactic restrictions in AP. This thesis also studies the restructuring of the syllabic margins and of the nucleus, with emphasis to ...

Esta tese objetiva estudar os processos fonológicos de sândi vocálico externo - ditongação, elisão de V1, crase e não realização ou apagamento de V2 - no Português Arcaico (PA) em 200 Cantigas de Santa Maria (CSM), século XIII, à luz das teorias não lineares. As CSM são uma coleção de 420 cantares em louvor da Virgem Maria compiladas em galego-português por Afonso X (1221 - 1284). Partimos da escansão, da contagem das sílabas poéticas dos versos das CSM e verificamos a localização dos acentos, elucidando dúvidas acerca da delimitação da palavra em PA e da resolução de encontros vocálicos em juntura vocabular. A metodologia busca abstrair da escansão dos versos em sílabas poéticas e do padrão de metrificação presente nas CSM os limites entre as palavras da língua daquela época, trazendo informações necessárias para uma pesquisa sobre a prosódia de línguas em relação às quais o contato com os falantes nativos não é possível. Os contextos de aplicação rítmicos e fonotáticos dos processos de sândi vocálico externo constituem o cerne de nosso estudo, que se expande, também, para a análise da ocorrência do hiato. Os resultados obtidos revelam que, na primeira fase da história da língua portuguesa, os processos fonológicos que desfazem a estrutura de hiato nos dias de hoje começaram a atuar ainda no PA. Ademais, esses eram expressivos no PA, por exemplo: a elisão, se comparada com o hiato (a permanência das duas vogais envolvidas no contexto de juntura vocabular), contém uma margem de aplicação muito próxima à manutenção de vogais, isto é, tanto a elisão quanto a manutenção do hiato eram produtivos naquele momento da língua. Por outro lado, a ditongação, a crase e o apagamento ou não realização de V2 consistiam em processos marginais, de contextos de aplicação bem mais restritos. Esses fatos se devem, muitas vezes, às restrições de natureza rítmica, prosódica ...
Keywords: Língua portuguesa; Canções sacras; Poesia medieval - História e crítica; Portuguese language